2013
DOI: 10.1096/fj.13-232686
|View full text |Cite
|
Sign up to set email alerts
|

Dosage of amyloid precursor protein affects axonal contact guidance in Down syndrome

Abstract: Amyloid precursor protein (APP), encoded on Hsa21, functions as a cell adhesion molecule (CAM) in axonal growth cones (GCs) of the developing brain. We show here that axonal GCs of human fetal Down syndrome (DS) neurons (and of a DS mouse model) overexpress APP protein relative to euploid controls. We investigated whether DS neurons generate an abnormal, APP-dependent GC phenotype in vitro. On laminin, which binds APP and β1 integrins (Itgb1), DS neurons formed enlarged and faster-advancing GCs compared to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 66 publications
2
24
2
Order By: Relevance
“…; Sosa et al . ). In this context, hippocampal pyramidal neurons derived from Ts65Dn mice and cultured on laminin substrate exhibit aberrant growth cones with large adhesive areas and abundant filopodia (Fig.…”
Section: The Implication Of App In Down Syndrome Neurodevelopmentmentioning
confidence: 97%
See 3 more Smart Citations
“…; Sosa et al . ). In this context, hippocampal pyramidal neurons derived from Ts65Dn mice and cultured on laminin substrate exhibit aberrant growth cones with large adhesive areas and abundant filopodia (Fig.…”
Section: The Implication Of App In Down Syndrome Neurodevelopmentmentioning
confidence: 97%
“…GC of these neurons are large and grow faster than those derived of euploid human neurons (Sosa et al . ). Since several genes are over‐expressed in DS, it becomes necessary to identify and differentiate the effects of APP from other CAMs on adhesion properties and the overall cell phenotype.…”
Section: The Implication Of App In Down Syndrome Neurodevelopmentmentioning
confidence: 97%
See 2 more Smart Citations
“…This very important concept may indeed account for the described cell-cell-adhesion properties of APP and subsequent signaling through homophilic interactions (reviewed in ref [37] ). This effect can be exacerbated in a dose-dependent manner during initiation of axonal growth pathfinding [74, 75] . More recent studies showed clear indication that APP dimerization would facilitate synapse formation [58, 76, 77] .…”
Section: The Role Of App Subdomains In Dimerization Processmentioning
confidence: 99%